Landscape of mobile genetic elements and their functional cargo across the gastrointestinal tract microbiomes in ruminants - Yijun Tang; Pengchao Zhan; Yingjian Wu; Tao Zhang; Di Yin; Yunlong Gao; Yueying Yu; Shengnan Qiu; Jiaqi Zhao; Xue Zhang; Zhe Ma; Yanting Chen; et al. (Microbiome)
Abstract Background Mobile genetic elements (MGEs) drive horizontal gene transfer and microbial evolution, spreading adaptive genes across microbial communities. While extensively studied in other ecosystems, the role of MGEs in shaping ruminant gastrointestinal microbiomes—especially their impact on diversity, adaptation, and dietary responsiveness—remains largely unexplored. This study systematically profiles MGE distribution and functionality across gastrointestinal regions in multiple ruminant species to advance our understanding of microbial adaptation. Results Across 2458 metagenomic samples from eight ruminant species, we identified 4,764,110 MGEs—a ~ 216-fold increase over existing MGE databases. These elements included integrative and conjugative elements, integrons, insertion sequences, phages, and plasmids, with mobilization patterns largely confined to closely related microbial lineages. The distribution of MGEs varied by GIT regions, often reflecting nutritional gradients. In a validation cohort, GH1-carrying plasmids enriched in carbohydrate-active enzymes were found to predominate in the stomach, showing notable responsiveness to forage-based diets. All annotated MGEs have been compiled into a publicly accessible database, rumMGE ( https://rummge.liulab-njau.com ), to support further research. Conclusions This study substantially expands the catalog of known MGEs in ruminants, revealing their diverse roles in microbial evolution and functional adaptation to dietary changes. The findings provide a valuable resource for advancing research on microbial functionality and offer insights with potential applications for enhancing ruminant health and productivity, through strategies aimed at modulating the microbiome in agricultural contexts. Video Abstract